2021
DOI: 10.4049/jimmunol.2000841
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Gain-of-Function Mutations Underlie Deficiency in Human Nonclassical CD16+ Monocytes and CD141+ Dendritic Cells

Abstract: Genetic analysis of human inborn errors of immunity has defined the contribution of specific cell populations and molecular pathways in the host defense against infection. The STAT family of transcription factors orchestrate hematopoietic cell differentiation. Patients with de novo activating mutations of STAT3 present with multiorgan autoimmunity, lymphoproliferation, and recurrent infections. We conducted a detailed characterization of the blood monocyte and dendritic cell (DC) subsets in patients with gain-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…High concentrations of IL-6 (250 ng/ml) skewed the development from DC1 toward DC2 [SIRP-α + ; fig. S13H (dark blue)] ( 51 , 52 ); however, low IL-6 concentrations (below 20 ng/ml) increased the expression of CD5 on both of these DC subsets [Fig. 6, H and I, and S13H (light blue)].…”
Section: Resultsmentioning
confidence: 99%
“…High concentrations of IL-6 (250 ng/ml) skewed the development from DC1 toward DC2 [SIRP-α + ; fig. S13H (dark blue)] ( 51 , 52 ); however, low IL-6 concentrations (below 20 ng/ml) increased the expression of CD5 on both of these DC subsets [Fig. 6, H and I, and S13H (light blue)].…”
Section: Resultsmentioning
confidence: 99%
“…For example, a putative DC subpopulation, identified transcriptomically and originally termed DC4 [92], is now considered to probably represent a subset of NC monocytes rather than DCs [46,93,94]. In addition, pathogenic variants in STAT3 have revealed this gene's role in regulating the production of both NC monocytes and the less-abundant cDC population, cDC1 [95]. Although we could detect the rare cDC1 population in our dataset, it became apparent only upon myeloid cell re-clustering (myeloid subcluster 7, marked by CLEC9A expression), and these cells were too sparse to enable us to accurately gauge their abundance or use for normalization purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The STAT3 pathway is activated downstream of numerous cytokines and growth factors, and it has been broadly implicated in both innate and adaptive immune pathways ( 50 ). Studies have demonstrated that germline STAT3 GOF variants lead to alterations in human monocyte and DC populations ( 51 ). Changes in relevant antigen presenting cell phenotype and chemokine expression may have an impact on local pTreg induction and/or localization ( 34 , 52 ).…”
Section: Discussionmentioning
confidence: 99%